Relative Advantages of Public Parks in Landscape Design Perspective in Ten Cities of East Java Province : Keunggulan Relatif Taman Publik dalam Perspektif Desain Lanskap di Sepuluh Kota Provinsi Jawa Timur - Suryaningsih, Dwie Retna; Thohiron, Mochamad; Nova, Marsela (Journal of Applied Plant Technology, 2023)
One way to determine the relative advantages of public parks is to carry out a landscape design perspective. This research aims to determine the influence of landscape elements and principles in public parks; to find out the application of landscape design elements in public parks; to find out the usefulness of applying landscape principles to public parks. This research was carried out in 10 Regency Cities in East Java, each with 3 public parks, so there are thirty public parks starting from March 2022 to August 2022. This research was carried out using quantitative and qualitative methods where all data was obtained in the form of results direct observation in the field through questionnaires. The data used in this research is research on landscape performance, the elements and principles of landscape design are the research object. The observed variables include 36 variables. The research took 30 respondents to be interviewed or fill out a questionnaire. The research results show that Sidoarjo Square, Malang Square, Ngegong Park, Apkasi Park, Obor Park, Trembesi Park and Bungkul Park occupy quadrant one. Meanwhile, Gersik Square, Batu Square, Batu City Green Park, Pasuruan City Park, Elderly Park, Ngronggo Park, Safari Park 2, Sekartaji Park and Tanjung Puri Park occupy the second quadrant. The parks that occupy quadrant 3 are Prambanan Gersik, Candra Wilwatikta Park, Kehati Park and Pelangi Park. Quadrant 4 consists of Pancasila Fort Park, Gapura Park, Kendedes Park and Mojokerto Square.